The Influence Of Compensation And Work Environment On Employee Performance At PT. Toyo Dies Indonesia: marketing Management - Elva Vhillia Aenina; Cecep Hermana (LPPM Universitas Buddhi Dharma, 2025)
This research discusses compensation, work environment and employee performance, with the aim of determining the effect of compensation and work environment on employee performance. This type of research is quantitative research by distributing questionnaires, the sample used in this research was 80 employees. The subjects of this research are employees of PT. Toyo Dies Indonesia. This research uses the multiple linear regression analysis method, this analysis technique is also classified as a collective model, so that the correlation coefficient between the independent variables and the dependent variable will be obtained, the significant level of the coefficient, the regression line equation, the correlation between predictor sub-variables and processed with SPSS version 22 . In this study there was no correlation between the independent variables. Compensation has a positive and significant effect on PT employee performance. Toyo Dies Indonesia. The work environment has a positive and significant effect on PT employee performance. Toyo Dies Indonesia. Compensation and work environment have a significant effect on PT employee performance. Toyo Dies Indonesia. It is known that the coefficient of determination (R-Square) is 0.582. This value states that Compensation (X1) and Work Environment (X2) are able to influence Employee Performance (Y) by 58.2%, the remaining 100% - 58.2% = 41.8% is influenced by variables outside this model. Among the Compensation (X1) and Work Environment (X2) variables which have a more dominant influence on the Employee Performance variable (Y), namely the Work Environment variable (X2).